Monitoring the Performance of Set Longlines Fishing Vessels at Fisheries Management Area 718 Indonesia - Yaya Hudaya; Ilham Ilham; Sutriyono Sutriyono; Mohamad Natsir (Bogor Agricultural University, 2021)
Abstract Catches reports by set longlines fishing vessels in the 718-fisheries management area (FMA) have been entered into the logbook reporting system since 2012. These vessels targeted reef and demersal fish. Set longlines is considered to be very efficient and productive for catching reef fish. This study aims to see the performance of set longlines vessels. The indicators used are CPUE and fuel efficiency. The results of the study show that the performance of set longlines vessels in the area is getting better and more efficient. Keywords: set longlines; reef fish; CPUE; fuel; efficient Abstrak Laporan hasil tangkapan oleh kapal penangkap rawai dasar di pengelolaan perikanan (WPP) 718 telah dimasukkan ke dalam sistem pelaporan logbook sejak 2012. Kapal-kapal rawai tesebut menargetkan ikan karang dan ikan demersal. Rawai dasar dianggap sebagai alat tangkap yang sangat efisien dan produktif untuk menangkap ikan karang. Penelitian ini bertujuan untuk melihat kinerja kapal rawai dasar. Indikator yang digunakan adalah CPUE dan efisiensi bahan bakar. Hasil penelitian menunjukkan bahwa kinerja kapal longline set di daerah tersebut semakin baik dan efisien. Kata kunci: rawai dasar; ikan karang; CPUE; bahan bakar; efisien